Development of Math Stook: An Exploration of Math Stories for Elementary School Students - Nafi’an, Muhammad Ilman; Moraninda, Gita Luthfiah; Rohmawati, Aulia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Research on the development of math story books for elementary school students still needs to be conducted further. Studies on the appropriate design, effectiveness, and effects on students' mathematical understanding are still limited, so more needs to be done. This research aims to develop Math Stook (Math Story Book) as a math learning media for elementary school students. The research method used is the RnD or Research and Development method with the ADDIE research model which consists of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation and interviews. The validity of Math Stook was evaluated by a group of validators, including media design experts, learning material experts, and pretest and posttest question experts. The results showed that Math Stook was rated as highly valid by the validators. In addition, this study measured the level of math comprehension of grade III students before and after using Math Stook, showing a significant increase. Although the N-Gain value fell into the “medium” category, this study concluded that Math Stook was effective in improving students' mathematical understanding. Recommendations for future research include further exploration of the effect of Math Stook on students' math skills, development of a version tailored to students' needs, as well as the use of a combined approach between quantitative and qualitative methods to explore its impact.